Phase transitions in the lattice model of intercalation - Mysakovych, T.S.; Krasnov, V.O.; Stasyuk, I.V. (Condensed Matter Physics, 2008)
The lattice model which can be employed for the description of intercalation of ions in crystals is considered
in this work. Pseudospin formalism is used in describing the interaction of electrons with ions. The possibility
of hopping of intercalated ions between different positions is taken into account. The thermodynamics of the
model is investigated in the mean field approximation. Phase diagrams are built. It is shown that at high values
of the parameter of ion transfer, the phase transition to a modulated phase disappears. В данiй роботi розглядається граткова модель, яка може бути застосована для опису iнтеркаляцiї iонiв в кристали. Використано псевдоспiновий формалiзм для опису взаємодiї електронiв з iонами та враховано можливiсть перескокiв iонiв мiж рiзними позицiями. Дослiджено термодинамiку моделi в наближеннi середнього поля. Побудовано фазовi дiаграми. Показано, що при великих значеннях iонного переносу фазовий перехiд у модульовану фазу зникає.